Sitosterolemia: Diagnosis, Metabolic and Hematological Abnormalities, Cardiovascular Disease and Management - Bastida, Jose María; Girós, María L.; Benito, Rocío; Janusz, Kamila; Hernández-Rivas, Jesús María; González-Porras, José Ramón (Current Medicinal Chemistry, 2019)
Sitosterolemia is a recessive inherited metabolic disorder of unknown prevalence, characterized by increased levels of plasma plant sterols. It is caused by 28 and 31 variants in ABCG5 and ABCG8 genes, respectively, and is characterized by a predisposition to hyperabsorption and accumulation of toxic levels of plant sterols in plasma. Its clinical picture is extremely heterogeneous. The main clinical features are tendinous and cutaneous xanthomas, arthritis or arthralgia, premature cardiovascular disease and atherosclerosis. These characteristics are shared with familial hypercholesterolemia (FH), making it possible for sitosterolemia to be misdiagnosed as homozygous FH, especially in pediatric patients. In such cases, a specific chromatography-based laboratory method is essential to differentiate sitosterol and cholesterol. Hematological abnormalities (hemolytic anemia and macrothrombocytopenia) may be present in 25-35% of patients, in whom it is usually associated with the main clinical features, as occurs in the 70% of the cases. In this context, the peripheral blood smear is essential and reveals giant platelets and stomatocytes. Only 21 causative variants in ABCG5/ABCG8 are associated with macrothrombocytopenia. Most physicians still do not recognize these hematological abnormalities or relate them to sitosterolemia. Patients may suffer long-term misdiagnosis of immune thrombocytopenia and be at high risk of receiving harmful therapies or of not benefitting from a low-cholesterol diet and/or from the gold standard treatment with ezetimibe. This drug reduces the levels of plasma plant sterols, provokes regression of xanthomas, and can alleviate hematological abnormalities. Finally, to identify genetic defects, recent advances in high-throughput sequencing, especially in the use of targeted sequencing of pre-specified genes, have begun to be incorporated in the first-line approach in the field of genetic disorders.
Keywords: sitosterol